Interaction between selenium and soil organic matter and its impact on soil selenium bioavailability: A review - Li, Zhe; Liang, Dongli; Peng, Qin; Cui, Zewei; Huang, Jie; Lin, Zhiqing (Geoderma, 2017)
The bioavailability of selenium (Se) in soil partly determines Se deficiency in human health. Soil organic matter (OM) is an important soil component that controls Se bioavailability. Better understanding of the interaction between selenium and soil organic matter will be scientifically and practically significant in terms of Se risk assessment in the environment and Se biofortification for human health. This paper gives an overview of current understanding on the interaction between soil OM and Se in soil–plant systems, highlighting that OM can immobilize Se by both biotic and abiotic mechanisms and reduce its bioavailability, but the release of OM-immobilized Se through mineralization should not be overlooked. In addition, soil organic amendments also have diverse effects on Se bioavailability. Future research directions and challenges on this topic have been addressed. •Soil organic matter retains Se in soil by both biotic and abiotic mechanisms.•The immobilization by soil organic matter significantly reduces Se bioavailability.•Se associated with soil organic matter can be slowly released into soil solution.•Soil organic amendments show diverse effects on soil Se bioavailability.•The influential factors of Se-organic matter interaction need to be further studied.